A critical and quantitative review of the stratification of particles during the drying of colloidal films. Issue 30 (19th July 2018) - Schulz, M.; Keddie, J. L.
Abstract : We review recent evidence for the operative mechanisms by which colloidal particles spontaneously stratify into layers within a drying film. Abstract : For a wide range of applications, films are deposited from colloidal particles suspended in a volatile liquid. There is burgeoning interest in stratifying colloidal particles into separate layers within the final dry film to impart properties at the surface different to the interior. Here, we outline the mechanisms by which colloidal mixtures can stratify during the drying process. The problem is considered here as a three-way competition between evaporation of the continuous liquid, sedimentation of particles, and their Brownian diffusion. In particle mixtures, the sedimentation of larger or denser particles offers one means of stratification. When the rate of evaporation is fast relative to diffusion, binary mixtures of large and small particles can stratify with small particles on the top, according to physical models and computer simulations. We compare experimental results found in the scientific literature to the predictions of several recent models in a quantitative way. Although there is not perfect agreement between them, some general trends emerge in the experiments, simulations and models. The stratification of small particles on the top of a film is favoured when the colloidal suspension is dilute but when both the concentration of the small particles and the solvent evaporation rate are sufficiently high. A higher particle size ratio also favours stratification by size. This review points to ways that microstructures can be designed and controlled in colloidal materials to achieve desired properties.